The reinvention of historical discourse in Zakes Mda's The heart of redness and Mike Nicol's This day and age - Saccaggi, Carolina Francesca (My University, 2008)
Post-apartheid South African fiction has been the subject of much heated debate. One specific aspect of this debate has revolved around the role of history in this fiction. This is linked to general concerns in the country around ways of understanding history, especially in relation to the Truth and Reconciliation Commission’s research into the past. Tracing the lines of debate which emerged out of the discussions around the Truth and Reconciliation Commission, this research report focuses on the way history is presented in two novels from the post-apartheid period. These novels are This Day and Age by Mike Nicol and The Heart of Redness by Zakes Mda. Each of the two novels concerns a specific incident from the past of South Africa, the Bulhoek massacre and the Xhosa cattle-killing respectively. Through tracing their intertextual relations with mainstream accounts of the historical events, the research shows how they interrogate these accounts. Detailed examination of the portrayal of history in each of the novels leads to conclusions being drawn about the way in which the novels conceive of such historical ideas as causality, linearity and responsibility. Finally, the research examines the role of prophecy in the novels, showing how in both of the texts prophecy can be read as an alternative explanation for events. The research endeavours ultimately to contribute to the body of critical thought concerning the analysis of post-apartheid South African fiction.
Keywords: South African fiction; Zakes Mda; Mike Nicol; historical fiction; prophecy